EVALUASI PENGARUH KADAR Na2O DAN K2O TERHADAP KUALITAS BUBBLE PADA KACA SODA LIME SILICA - Risqi Kurniawan (JURNAL KONVERSI, 2018)
Tight competition in soda lime silica glass industry cause quality improvement become very important, bubble in flat glass is one of quality parameter which have to improve. So it’s need effort to improve bubble quality in glass. One of influence factor for bubble quality is R2O content in glass, where R2O is sum of N2O and K2O. This research perform in flat glass manufacture type soda lime silica glass with capacity 500 t/d. in this research adjust R2O content from 13.5% to 13.8%, by this adjustment bottom dog house suhu became increase from about 1100 oC to 1120 oC, and also glass viscosity which represent by log y-2 changed from 1460 oC down became 1445 oC. From these two parameter, bubble count became increase from 400 pcs/hour to 1700 pcs/hour, these things are caused by decrement of glass viscosity, forward current of molten glass became faster, so bubble can’t be removed by fining or refining and carried to forming process and finally became defect in glass.